Bintang Donor: Pembuatan Aplikasi Relawan Donor Darah Universitas Sumatera Utara dan Penggalangan Relawan Sebagai Manifestasi Generasi Bintang yang Peduli Kemanusiaan - Hatta Ridho; Husni Thamrin; Edi Sumarno; Arief Marizki Purba (Pusat Pengembangan Pendidikan dan Bakat Indonesia/Education and Talent Development Center of Indonesia, 2025)
Blood, as a vital component, has essential functions in the human body, including nutrient circulation, oxygen transport, and hormone distribution. A shortage of blood supply can be fatal, making an adequate blood supply in healthcare facilities crucial for saving patients' lives and maintaining the continuity of the medical service system. Despite its clear importance, challenges in meeting blood needs still frequently occur, primarily due to a lack of public awareness about the urgency and benefits of blood donation, as well as uneven understanding of the process and donor eligibility criteria. This phenomenon is exacerbated by fluctuating donation rates, an aging population demographic, and socioeconomic shifts that impact the sustainable availability of donors. The partner in this community service is the Indonesian Red Cross (PMI) of Medan City, located at Jl. Palang Merah No. 17 Medan. PMI Medan City offers several services such as ambulance, disaster management, training, social service units, and blood donation. The partner's problems are the public's lack of awareness of the importance of blood donation, minimal socialization and information about blood donation, and unstable blood stock availability, making it important to maintain the amount of available blood stock. Based on the partner's problems, the solutions offered in this service are raising awareness, capacity building, and empowering the community thru the creation of the Bintang Donor application and the formation of blood donation volunteers. The benefits obtained are that by forming blood donation volunteers, knowledge, awareness, and public health are increased thru blood donation, blood stock availability can be maintained so that it remains stable, and it becomes easier for the public to obtain information and blood donation locations. The planned outputs of this program are: a journal of the activity results, a video of the activity implementation, publications in mass/online media, and Intellectual Property Rights (IPR).